Influencia del clima organizacional en la satisfaccion laboral del personal operativo en el area de operaciones de la caja municipal de ahorro y crédito de trujillo s.a. agencia españa, 2013 - Alvarez Saldaña, Fiorella Mariella (2015)
This research was conducted in order to know the Influence of the Organizational Climate on Job Satisfaction of the operational staff in the Area of Operations in Caja Municipal de Ahorro y Crédito (Municipal savings and credit bank) Trujillo SA Agency Spain, 2013. The research is primarily descriptive used the ethnographic methods, analytic-synthetic and statistician, using the techniques of observation, interview and survey. The research was conducted in a financial company Municipal Savings and Credit Trujillo SA Workers in the area of operations of the company declare that there is good communication between colleagues, this due to the ongoing dialogue to improve their work; in that case, having friendly colleagues who give support would originate a high job satisfaction, but on the other hand, the behavior of managers and / or immediate supervisors is perhaps one of the most important factors that increase the level of job satisfaction. Among the findings is that the operational staff said that only sometimes feel satisfied with their work, failing to reach the target set by the company, are frustrated and consequently fall into a negative attitude becomes a circle vicious; not everyone feels identified with the company . What I got in this research supports the conclusion that if there is an influence of organizational climate on job satisfaction of operational staff, through interpersonal relationships , communication between them as motivation. KEY WORDS: Organizational climate, job satisfaction, interpersonal relationships, communication and motivation.